ANALISIS BAURAN PEMASARAN DALAM MENINGKATKAN PENJUALAN PRODUK KRIPIK JAMUR MALLAWA (Studi Kasus Kelompok Tani Hutan Samber di Kecamatan Mallawa Kabupaten Maros) - Ida Rosada; Nuraeni Nuraeni; Aqifah Magfirah Annas (Journal TABARO Agriculture Science, 2022)
This study aims to describe the production process of Mallawa mushroom chips, analyze the amount of production and income of Mallawa mushroom chips, and describe the marketing mix of Mallawa mushroom chips, as well as analyze the feasibility of the Mallawa mushroom chip business of the Samber Forest Farmers Group in Mallawa District, Maros Regency. The population is consumers who purchase Mallawa mushroom chip products with the criteria of consumers who have bought or consumed Mallawa mushroom chips at least once, are willing to be interviewed, and are 17 years and over. The sampling technique used was purposive sampling with 30 respondents. The production process for Mallawa mushroom chips, starting from the preparation of raw materials, weighing the oyster mushrooms, shredding the oyster mushrooms, washing the shredded oyster mushrooms and then squeezing them, the process of mixing the ingredients, coating the oyster mushrooms with flour dough, the frying process, to the packaging process. . Production was carried out in two stages, namely the first produced as many as 800 packages, the second stage of production produced as many as 700 packages. A total of 1,500 packages are produced in a month and the monthly income is IDR 2,598,967. The marketing mix including product, price, promotion, and place has a score of 951 in the category of not implementing the marketing mix. Processing business feasibility, R/C-Ratio of 1.4 means the product is profitable and feasible to develop.